Effects of an Educational Intervention on Male Students' Intention to Quit Water Pipe Smoking: an Application of the Theory of Planned Behavior (TPB) and Health Action Process Approach (HAPA) - Hamid Joveini; Tahereh Dehdari; Masoumeh Hashemian; Mina Maheri; Reza Shahrabadi; Alireza Rohban; Ali Mehri; Hasan Eftekhar Ardebili (Hamadan University of Medical Sciences, 2020)
Aims: Water pipe smoking has become very popular among young people. Regarding to the increasing prevalence of water pipe smoking among students, the aim of this study was to determine the effects of an educational intervention based on Theory of Planned Behavior (TPB) and Health Action Process Approach (HAPA) on male students' intention to quit water pipe smoking. Materials & Methods: This semi-experimental study was conducted on 150 male students of the Islamic Azad University of Sabzevar-Iran, in 2017 who were selected by simple random sampling method and allocated to two control and intervention groups (75 people in each group). Data collection tool included a demographic information questionnaire and a researcher-made questionnaire based on motivational phase constructs of health action process approach and theory of planned behavior. Intervention group participants received six sessions of education (45 minutes per session). Both groups completed questionnaires in baseline and one month after the intervention. Data were analyzed in SPSS 23 software using statistical tests. Findings: Before the intervention, there was no significant difference in the mean scores of the constructs of risk perception, outcome expectancy, action self-efficacy, attitude, subjective norms, perceived behavioral control, and behavioral intention to quit water pipe smoking between the two groups (p>0.05). However, after the intervention, these differences were significant except attitude (p<0.05). Also, after the intervention, intention to quit water pipe smoking in the students of intervention group had significant difference compared to the control group (p=0.004). Conclusion: The educational intervention based on Theory of Planned Behavior (TPB) and Health Action Process Approach (HAPA) is effective in creating the intention to quit water pipe smoking among students